In Vivo Chondrogenesis in 3D Bioprinted Human Cell-laden Hydrogel Constructs - Möller, Thomas (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: The three-dimensional (3D) bioprinting technology allows creation of 3D constructs in a layer-by-layer fashion utilizing biologically relevant materials such as biopolymers and cells. The aim of this study is to investigate the use of 3D bioprinting in a clinically relevant setting to evaluate the potential of this technique for in vivo chondrogenesis. METHODS: Thirty-six nude mice (Balb-C, female) received a 5- × 5- × 1-mm piece of bioprinted cell-laden nanofibrillated cellulose/alginate construct in a subcutaneous pocket. Four groups of printed constructs were used: (1) human (male) nasal chondrocytes (hNCs), (2) human (female) bone marrow–derived mesenchymal stem cells (hBMSCs), (3) coculture of hNCs and hBMSCs in a 20/80 ratio, and (4) Cell-free scaffolds (blank). After 14, 30, and 60 days, the scaffolds were harvested for histological, immunohistochemical, and mechanical analysis. RESULTS: The constructs had good mechanical properties and keep their structural integrity after 60 days of implantation. For both the hNC constructs and the cocultured constructs, a gradual increase of glycosaminoglycan production and hNC proliferation was observed. However, the cocultured group showed a more pronounced cell proliferation and enhanced deposition of human collagen II demonstrated by immunohistochemical analysis. CONCLUSIONS: In vivo chondrogenesis in a 3D bioprinted human cell-laden hydrogel construct has been demonstrated. The trophic role of the hBMSCs in stimulating hNC proliferation and matrix deposition in the coculture group suggests the potential of 3D bioprinting of human cartilage for future application in reconstructive surgery.